Prevalence of COVID-19 Virus Infection in Semnan province - Elahe Jandaghi; Maral Hemati; Maryam Mohammadlou; Jafar Jandaghi; Majid Mirmohammadkhani; Navid Danaei; Parviz Kokhaei (Iranian Journal of Immunology, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS- CoV-2) causing a human pandemic disease named COVID-19 has become a major global health concern. Iran as one of the most affected countries needs unprecedented effort for monitoring and evaluation of COVID-19. Objective: To determine the seroprevalance of COVID-19 in Semnan province North-East of Iran. Methods: Six hundred people were randomly selected using the "SIB data-base". From 1 to 30 June, 2020, 153 participants of Semnan population were enrolled. Blood, nasopharyngeal and oropharyngeal samples were obtained. Prevalence of IgM and IgG antibodies were ascertained using ELISA and Real-Time PCR was conducted to evaluate viral load. Estimates of prevalence were standardized by age and sex, based on the 2015 national census of Semnan province. Results: Seroprevalence showed no difference between females and males and no significant association between age and seropositivity. Among total participants, the age and sex adjusted prevalence of SARS-CoV2 infection was 19.3% (95% CI, 14.0-26.7 per 100 persons). Approximately 10% of participants had detectable antibodies but showed a negative-PCR result. However, approximately 80% of participants did not show an evidence of infection. Conclusion: The majority of the population in Semnan province has no detectable antibodies to SARS-CoV-2. Therefore, Semnan is considered a SARS-CoV-2 susceptible area. These results emphasize the need for maintaining public health measures to tackle the new epidemic wave.